Reconstructing Pesantren Pedagogy: Integrating Social-Emotional Learning (SEL) and Sayyidah ‘Ā’ishah’s Intellectual Rigor to Enhance Student Agency - Shafa Alistiana Irbathy; Naomi Fahma (CV. Bimbingan Belajar Assyfa, 2025)
In today's era of digital disruption, critical literacy skills and emotional intelligence are essential competencies for students to navigate complex information. Dialogic and reflective teaching are seen as creative strategies to enhance these skills in Islamic educational environments. This research is motivated by the dominance of traditional teaching patterns in Islamic boarding schools (pesantren), which often emphasize absolute obedience (ta'dzim), thus risking inhibiting students' critical reasoning and psychomotor independence. While previous research has primarily evaluated the purely cognitive aspects of hadith transmission, this study evaluates the impact of integrating prophetic values ​​on the development of students' affective and social behavior. The main objective of this research is to construct a new pedagogical model that synergizes the Social-Emotional Learning (SEL) framework with the intellectual legacy of Sayyidah 'Ā'ishah r.a. Using a qualitative library research design with content analysis techniques, this study maps 'Ā'ishah's pedagogical behavior into the five core CASEL competencies through documentation tools of classical texts and contemporary literature. The results of the study indicate that this integration has a positive impact on improving students' self-efficacy and relational skills through scaffolding mechanisms based on tabayyun (clarification) and baḥth al-‘ilm (scientific inquiry). The findings confirm that an empathetic approach does not diminish intellectual rigor, but rather strengthens the courage to express opinions without eroding moral values. In conclusion, the